Study of changes in the surface structure of tungsten irradiated by helium plasma - Л.Г. Сулюбаева; Б.К. Рахадилов; Е. Найманқұмарұлы; М.Б. Баяндинова; Н. Мұқтанова; Н.Е. Бердимуратов (Қарағанды университетінің хабаршысы. Физика сериясы)
One of the important aspects is the interaction of plasma with the surface of a material, especially in the conditions of a fusion facility. The current work presents the preliminary results of the study of tungsten surface structure modification under helium plasma irradiation. A small-sized linear simulator KAZ-PSI with a plasma-beam setup was designed and assembled, where helium was used as a working gas. The main elements of the linear plasma simulator are an electron beam gun with a LaB6 cathode, a plasma-beam discharge chamber, an interaction chamber, a target device, and an electromagnetic system consisting of electromagnetic coils. It was revealed that under irradiation on the surface of the samples there is a relief with defective structure consisting of chaotically arranged ledges and pits of various shapes with average size (100‒600) nm and pore sizes (0.1‒1.5) μm with visible areas of flaking and sputtering. It was found that when the negative potential on the target is varied by –500V/–1000V/–1500V, the formation of dislocation with chaotic and cellular structure of tungsten with an average grain size of (1‒25) μm is observed; it was revealed that the total values of elastic and plastic components of deformation across the tungsten grain differ from each other by about 2.5 times.